Pengaruh Sistem Pemberian Pelayanan Keperawatan Profesional Metode Tim Terhadap Kepuasan Pasien dan Kepuasan Perawat di Instalasi Rawat Inap Rumah Sakit Umum Daerah 45 Kuningan - Abdal Rohim; Aria Pranatha (Jurnal Ilmu Kesehatan Bhakti Husada: Health Sciences Journal, 2017)
One of care forms which mostly influence the patient satisfaction level in hospital is nursing care. The application of SP2KP (Professional Nursing Care Delivery System) has become one of the leverage power and very effective to increase the excellent care. The development of excellent nursing care uses the application of nursing team of SP2KP. If the responsibility or nurses’ roles (documenting, operant conditioning, supervising, and medicine centralizing) are not conducted well, it means that the nurses’ performance decreases. The objective of the research is to analyze the effect of the team nursing method application of SP2KP on patient satisfaction and nurse satisfaction at RSUD 45 Kuningan. The research method used was quantitative with quasi-experimental design which was non equivalent without control group design. The subject of the research was all patients and nurses in Bougenvile and Cempaka Room. The sample collection technique used was total sampling. The instrument of the research used was questionnaire. Based on the result of data normalization test of normal research, the data analysis used was T-test. The result of the research stated that tthere was a significant effect of the SP2KP application on patient satisfaction and nurse satisfaction in Bougenville, Cempaka and Flamboyan Room in RSUD ’45 Kuningan with p value = 0.00. It is suggested that chief nursing officer should monitor and evaluate comprehensively so that the application of SP2KP can be conducted very well and increase the quality of nursing care.